2012
DOI: 10.3892/or.2012.2143
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a dose-intensified CHOP (Double-CHOP) regimen for peripheral T-cell lymphomas

Abstract: Peripheral T-cell lymphomas (PTCLs) are a rare and heterogeneous group of non-Hodgkin lymphomas, often resulting in poor prognoses. The CHOP chemotherapy regimen, which includes cyclophosphamide, doxorubicin, vincristine and prednisone, has been used previously to treat other types of lymphomas. Here, we examined the efficacy and safety of a dose-intensified CHOP regimen (Double-CHOP), which was followed by autologous stem-cell transplantation (ASCT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…A number of retrospective [11][12][13][14][15][16][17][18]29] and prospective [8][9][10]22,30,31] studies have reported an apparent outcome advantage from the use of upfront HDT/ASCT in PTCL patients with chemosensitive disease. In the present study, less than half of PTCL patients were considered eligible for inclusion in CTs with multiagent chemotherapy followed by SCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of retrospective [11][12][13][14][15][16][17][18]29] and prospective [8][9][10]22,30,31] studies have reported an apparent outcome advantage from the use of upfront HDT/ASCT in PTCL patients with chemosensitive disease. In the present study, less than half of PTCL patients were considered eligible for inclusion in CTs with multiagent chemotherapy followed by SCT.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, large phase II trials testing upfront high-dose chemotherapy (HDT) and autologous SCT (ASCT) have shown good feasibility and a possible beneficial effect on clinical outcome [8][9][10]. With the obvious caveat of patient selection, retrospective studies also seem to support this impression, particularly in patients exhibiting chemosensitive disease [11][12][13][14][15][16][17][18]. National guidelines, such as those from the National Comprehensive Cancer Network, include HDT/ASCT as a recommended option for consolidation after first remission in patients with histologies other than anaplastic lymphoma kinase (ALK)-positive anaplastic large cell lymphoma (ALCL) [19].…”
Section: Introductionmentioning
confidence: 99%
“…1 In our previous study, we developed dose-intensified CHOP therapy, followed by high-dose chemotherapy (HDC) with autologous hematopoietic stem cell transplantation (auto-HSCT) or high-dose methotrexate (HD-MTX) for patients with high-risk PTCLs (double-CHOP protocol). 2 We treated 28 patients with PTCLs using double-CHOP from 1996 to 2012, excluding those with anaplastic large cell lymphoma kinase-positive anaplastic large cell lymphoma (ALK + ALCL). 2 In the study, the complete remission (CR) rate with double-CHOP, 3-year OS rate, and 3-year relapse-free survival rates…”
mentioning
confidence: 99%
“…were 68%, 68%, and 60%, respectively. 2 However, comparative studies have not proven any dose-intensified chemotherapies against PTCLs to be superior to conventional CHOP with or without etoposide. 3,4 Pirarubicin, or tetrahydropyranyladriamycin (THP), is a unique anthracycline synthesized from derivatives of daunorubicin and adriamycin.…”
mentioning
confidence: 99%
See 1 more Smart Citation